The Life Chances of Young Poles - the Problem of the Sense of Agency - Izabella Maria Łukasik (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
Entering adulthood is a process which for many people becomes a source of disappointment and frustration. If young people aren't prepared for the encounters with difficulties which can be met while searching for their own place in life during their school education, they become helpless and have a "cracked" reflectivity, as noted by Margaret S. Archer. At the same time one cannot ignore the gradual emergence of a new social class - the precariat - a dangerous class, as we are warned by Guy Standing. This group consists predominantly of young adults who are often seeking work far from home without any guarantee of employment. The role played by the sense of agency is indisputable. Life chances depend on whether one acts with his/her free will. The only hope for proper social functioning is community building because, according to Charles Taylor, individualism, the predominance of instrumental rationality, and the lack of active citizenship constitute a kind of contemporary threat.